Perancangan Jobsheet Mikroprosesor Zilog 80 Menggunakan Mikroprofesor MPF-1 - Endi Permata; Irwanto (JURNAL PTI (PENDIDIKAN DAN TEKNOLOGI INFORMASI) FAKULTAS KEGURUAN ILMU PENDIDIKAN UNIVERSITA PUTRA INDONESIA "YPTK" PADANG, 2022)
An understanding of the microprocessor is needed for the development of a microcomputer. The Z80 microprocessor was chosen as a learning medium because the programming architecture is still basic. This study uses R&D (Research and Development) and the ADDIE (Analyze, Design, Development, Implement, Evaluate) development model. The final product of this research is learning media in the form of Zilog 80 Microprocessor Jobsheet. students in microprocessor courses and the implementation of microprocessor practicums so that they can run effectively. The research results obtained for the Zilog 80 Microprocessor Jobsheet based on the assessment of media experts get a total percentage of 81.2% and are included in the very eligible category, then the results of the assessment based on material experts get a total percentage of 87.5% and fall into the category very worthy. In addition, the results of questionnaires from users of the Zilog 80 Microprocessor Jobsheet also received a total percentage of 85% and were included in the very eligible category. Based on the results of the assessment obtained, it can be concluded that the Zilog 80 Microprocessor Jobsheet can be said to be eligible as a learning medium